(untitled) (Colombia Medica, 1986)
The present case showed a patient with tetralogy of Fallot and a "relative hypochromic microcytic anemia" who had a cerebrovascular accident, ischemia, and femoral artery occlusion. Literature regarding thrombotic episodes in cyanotic heart disease has been reviewed.